Acute measles encephalitis in partially vaccinated adults. - Annette Fox; Than Manh Hung; Heiman Wertheim; Le Nguyen Minh Hoa; Angela Vincent; Bethan Lang; Patrick Waters; Nguyen Hong Ha; Nguyen Vu Trung; Jeremy Farrar; Nguyen Van Kinh; Peter Horby (PLoS ONE)
Background The pathogenesis of acute measles encephalitis (AME) is poorly understood. Treatment with immune-modulators is based on theories that post-infectious autoimmune responses cause demyelination. The clinical course and immunological parameters of AME were examined during an outbreak in Vietnam. Methods and findings Fifteen measles IgM-positive patients with confusion or Glasgow Coma Scale (GCS) score below 13, and thirteen with uncomplicated measles were enrolled from 2008-2010. Standardized clinical exams were performed and blood collected for lymphocyte and measles- and auto-antibody analysis. The median age of AME patients was 21 years, similar to controls. Eleven reported receiving measles vaccination when aged one year. Confusion developed a median of 4 days after rash. Six patients had GCS <8 and four required mechanical ventilation. CSF showed pleocytosis (64%) and proteinorrhachia (71%) but measles virus RNA was not detected. MRI revealed bilateral lesions in the cerebellum and brain stem in some patients. Most received dexamethasone +/- IVIG within 4 days of admission but symptoms persisted for ≥3 weeks in five. The concentration of voltage gated calcium channel-complex-reactive antibodies was 900 pM in one patient, and declined to 609 pM ∼ 3 months later. Measles-reactive IgG antibody avidity was high in AME patients born after vaccine coverage exceeded 50% (∼ 25 years earlier). AME patients had low CD4 (218/µl, p = 0.029) and CD8 (200/µl, p = 0.012) T-cell counts compared to controls. Conclusion Young adults presenting with AME in Vietnam reported a history of one prior measles immunization, and those aged <25 years had high measles-reactive IgG avidity indicative of prior vaccination. This suggests that one-dose measles immunization is not sufficient to prevent AME in young adults and reinforces the importance of maintaining high coverage with a two-dose measles immunization schedule. Treatment with corticosteroids and IVIG is common practice, and should be assessed in randomized clinical trials.